How Finnish Adolescents Understand History: Disciplinary Thinking in History and Its Assessment Among 16-Year-Old Finns - Jukka Rantala (MDPI AG, 2012)
The success of discipline-based teaching requires an interplay between substantive and procedural knowledge. In Finland, disciplinary thinking was included in the National Core Curriculum and in the final assessment criteria a decade ago, which meant a change in history teaching. The outcome of this change is examined in the article with the help of a national-level history test that was conducted in 2011 among 16-year-old Finns. In the test, the adolescents fared moderately well in tasks involving substantive knowledge but more poorly in tasks which measured the mastering of procedural knowledge. In particular, the interplay between these proved to be difficult for the students. The students' knowledge was found to correspond with the earlier curriculum rather than the objectives of the present one, revealing that not all of the teachers were teaching in accordance with the present demands.